Strategies for inclusion physical education for everyone - Lieberman, Lauren J. 1965-; Grenier, Michelle 1956-; Houston-Wilson, Cathy 1962- (Human Kinetics, 2025)
"The purpose of this book is to provide physical education teachers with the information and tools necessary for the successful inclusion of students with disabilities into their programs. This product is designed to serve as a higher education textbook as well as a professional development or continuing education resource"--Provided by publisher.